Lymphatic Injury After Vertebral Column Resection from a Posterior Approach for Spinal Deformity Correction: A Case Report. Issue 4 (14th October 2021) - Ladd, Bryan; Jones, Kristen; Polly, David
Abstract : Case: We describe a case of lymphatic injury that occurred during a 2-level vertebral column resection for spinal deformity correction from a posterior-only approach. Large surgical drain volume output with laboratory findings of high levels of triglycerides and lymphocytes prompted conservative treatment with an elastic wrap bandage and a "no fat" diet. The patient responded to the treatment with no sequelae noted. Conclusion: Lymphatic complications are rare in spine surgery. All reported cases are associated with anterior approaches. The lymphatic injury presented here demonstrates the potential for this complication to occur during posterior-only approaches as well.